Teknik Menghindari Kerusakan Zat Aktif Akibat Paparan Suhu dan Kelembapan - Helen Fitri Novianti; Dini Auliya Azmi; Elisabeth Weya; Siti Jamilah; Muhamad Reza Pahlevi; Garnadi Jafar; Novaliana Devianti Sagita (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Deterioration of active ingredients due to exposure to temperature and humidity is a challenge in the development and storage of products containing active ingredients in the pharmaceutical industry. Exposure to high temperatures can accelerate the thermal degradation of active ingredients through mechanisms such as oxidation, decomposition, or Maillard reactions, resulting in decreased efficacy of active ingredients and the generation of undesirable degradation products. Meanwhile, high humidity also plays a role in accelerating the hydrolysis reaction of water-sensitive active ingredients, such as esters or amides, which reduces the chemical stability of the active ingredients. The combination of high temperature and high humidity often results in more complex degradation reactions compared to isolated temperature or humidity conditions, which can accelerate the decline in efficacy of active ingredients. Therefore, this article aims to explore various methods to view the stability of active ingredients under certain conditions, as well as provide recommendations for the development of more efficient formulations and storage strategies to maintain the stability and efficacy of active ingredients throughout the product's shelf life.